Nikah Mut’ah dalam Persepektif Kompilasi Hukum Islam dan Syi’ah - Rohim Rohim; Ahmad Hidayat; Aspandi Aspandi (Pusat Riset dan Inovasi Nasional, 2025)
Basically, In order to have a lasting, contented, and successful family, a man and a woman must physically and spiritually join via marriage. This marriage contract gives both parties the right to enjoy a relationship in accordance with the Shari'a. This study aims to reveal and compare the views of scholars from various schools of thought (Hanafiyah, Malikiah, Syafi ivah, and Hanabilah) regarding temporary marriage, namely “Nikah Mutah,” which is viewed from the legal arguments of each scholar. The descriptive technique was used in this study. which describes the thoughts of previous scholars regarding mut'ah marriage and the legal basis they used. The study's findings indicate that the ulama agree to prohibit mutah marriages absolutely, based on several propositions and the Qur'an, such as surah An-Nisa (4) 24. Al-Mu'minun (23): 5-7, and At- Thalaq (65) 1, as well as various hadiths. The consensus of scholars also supports the prohibition of mut'ah marriage. On the other hand, the Svi'ah view regarding mut'ah marriage is that this marriage is permitted, referring to QS An-Nisa (4): 24, which is considered to be related to temporary marriage. This mut'ah marriage allowed during the period the beginning of Islamic history, and some narrations from Shiite sources indicate that the law on mut'ah marriage was never canceled by the Koran or the Prophet Muhammad SAW. According to Shiite scholars, the prohibition on mut'ah marriage occurred during the time of Caliph Umar bin Khattab, which they consider as an ijtihad.